2024
DOI: 10.1002/mnfr.202300443
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Metabolite TMA May Mediate the Effects of TMAO on Glucose and Lipid Metabolism in C57BL/6J Mice

Xiao‐Yue Li,
Zhu‐Lin Yu,
Ying‐Cai Zhao
et al.

Abstract: ScopeGut microbiota can convert a variety of alkaloids and TMAO into TMA, which is then transported by the blood to the liver, and converted into TMAO. In recent years, TMAO has attracted wide attention as a metabolic risk factor in cardiovascular disease, diabetes, and other diseases. However, it is still unclear about the role of gut microbial metabolite TMA in the adverse health impacts of TMAO.Methods and resultsMale C57BL/6J is treated with intraperitoneal (i.p.) or oral TMAO for 8 weeks, the area under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…TMAO has been shown to have a causal relationship with atherosclerosis and kidney function. , While for others, only correlations were observed, which means the enhanced TMAO level may be only a feedback mechanism against disease development or could be used as a biomarker rather than an inducer. Moreover, there are animal studies shown that TMA, not TMAO, is responsible for the adverse effects. ,, For different diseases, it further investigation.…”
Section: Tmao and Chronic Disease Riskmentioning
confidence: 95%
See 3 more Smart Citations
“…TMAO has been shown to have a causal relationship with atherosclerosis and kidney function. , While for others, only correlations were observed, which means the enhanced TMAO level may be only a feedback mechanism against disease development or could be used as a biomarker rather than an inducer. Moreover, there are animal studies shown that TMA, not TMAO, is responsible for the adverse effects. ,, For different diseases, it further investigation.…”
Section: Tmao and Chronic Disease Riskmentioning
confidence: 95%
“…Moreover, there are animal studies shown that TMA, not TMAO, is responsible for the adverse effects. 100,108,114 For different diseases, it further investigation.…”
Section: Tmao With Nephropathymentioning
confidence: 99%
See 2 more Smart Citations